ADHD Symptoms in Adolescents' Everyday Life: Fluctuations and Symptom Structure Within and Between Individuals. Issue 8 (June 2020) - Schmid, Johanna; Stadler, Gertraud; Dirk, Judith; Fiege, Christiane; Gawrilow, Caterina
Objective: This study investigated whether self-reported ADHD symptoms fluctuate substantially within adolescents from day to day, and examined the underlying symptom factor structure on a within- and between-person level.Method: Adolescents ( N = 166) rated their ADHD symptoms over the phone on eight consecutive evenings (total ratings: n = 1, 264).Results: ADHD symptoms showed substantial fluctuations within adolescents from day to day, as indicated by within-person standard deviations and intraclass correlation coefficients. Both a two-level factor model with three correlated factors (inattention, hyperactivity, impulsivity) and a two-level bifactor model with a general ADHD symptom factor and a specific inattention factor provided acceptable to good accounts of the structure underlying daily ADHD symptom ratings on the between- and the within-person level.Conclusion: The study demonstrates that adolescents' ADHD symptoms fluctuate from day to day and highlights the need for intensive diagnostic processes with repeated symptom assessments and interventions that address symptom fluctuations.